Laser-Based Micro- And Nanoprocessing XIV 2020
DOI: 10.1117/12.2545623
|View full text |Cite
|
Sign up to set email alerts
|

Effect of process parameters on surface texture generated by laser polishing of additively manufactured Ti-6Al-4V

Abstract: Although there have been numerous attempts to define how different laser polishing parameters affect the generated surface roughness, there has been no detailed investigation of how their effects can be combined to optimize the process. This paper applies statistical analysis to model and predict the resulting surface roughness for laser post-processing of components made of Ti-6Al-4V and produced by laser powder bed fusion. This model is based on analysis of a wideranging experimental programme investigating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The confidence levels for the axial feed rate, the number of repetitions, and the laser power were very low. However, the previously mentioned study resulted in a much better fit for the surface roughness model and showed the same order of parameter relevance as observed for the HAZ depth in the current work [48].…”
Section: Model Coefficient Estimationsupporting
confidence: 84%
See 1 more Smart Citation
“…The confidence levels for the axial feed rate, the number of repetitions, and the laser power were very low. However, the previously mentioned study resulted in a much better fit for the surface roughness model and showed the same order of parameter relevance as observed for the HAZ depth in the current work [48].…”
Section: Model Coefficient Estimationsupporting
confidence: 84%
“…In each plot, the remaining parameters are kept constant. The plots of the dependent variables plotted on the Y-axis in the following figures show how sensitive The poor outcomes obtained for the Ra were associated with smaller data sets and the presence of high outliers; better results were obtained using the same procedure but with a larger set of input data [48]. The regression model for surface roughness has only the focal offset and the scanning speed statistically relevant at the 95% confidence level, the former being slightly more significant than the latter.…”
Section: Parameters Interactionmentioning
confidence: 99%
“…The parameter set, utilized in this work, was selected based on previous process optimization and material characterization studies for resulting properties. Table 1 introduces the adopted parameters [29,30].…”
Section: Continuous Wave Lasermentioning
confidence: 99%
“…In addition to material development, additive manufacturing offers great design freedom in component design, which can be used, for example, for the development of load-optimized designs based on the bionic principle [5]. To add up to the versatility of additive manufacturing, laser post-processes can be used to modify the resulting surfaces of parts produced with such technology [6][7][8][9]. The different types of laser sources commercially available assure their suitability in a wide range of applications, with continuous wave (cw) lasers being often used for reduction of surface roughness, while pulsed lasers being applied in the modification of surface functionalities and to enhance the geometry accuracy.…”
Section: -Introductionmentioning
confidence: 99%